(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The paper aims to investigate, using a comparative methodological approach, the ongoing relationship between the legal recognition of gender identity and the legal recognition of parenthood. The purpose of the paper is twofold: first, to highlight the points of intersection between these two forms of legal recognition, and second, to examine the most relevant legal issues that arise from these points of contact.